UNHCR Synergy with Nigerian Government and the Security Concerns of Vulnerable Cameroonian Anglophone Refugees in Cross River State, Nigeria, 2017-2023 - Oko, Thomas Odey (Journal of Contemporary International Relations and Diplomacy, 2024)
The influx of Cameroonian refugees seeking humanitarian protection in Nigeria indicates the severity of the conflict and the desperate conditions that force people to flee their homes. The separatist movements in Anglophone Cameroon and clashes with government forces have led to widespread violence, displacement, and human rights abuses. As a result, over 60,000 refugees have crossed into Nigeria between 2017 and 2023. However, while studies have explored the causes of the conflict and the humanitarian challenges faced by the refugees in their various settlements, this research assesses how the synergy between the United Nations High Commissioner for Refugees (UNHCR) and the Nigerian Government has impacted the security concern of Cameroonian refugees in Cross River State, Nigeria. Theoretically, the study was anchored on the Global Governance Theory. Survey and documentary methods were used to gather data. Data were analyzed using thematic analysis, logical deductions and statistical inferences. Findings include underfunding of the UNHCR and the apparent inability of the Nigerian Government to tackle the security concerns of the vulnerable Cameroonian refugees in Cross River State. The study recommends adequate funding to improve basic services and infrastructures within the refugee settlements.